Nonverbal Neutrality Norm: How Experiencing Trauma Affects Journalists' Willingness to Display Emotion. Issue 1 (1st January 2023) - Deavours, Danielle
ABSTRACT: The neutrality norm, journalists' ability to remove their opinions and emotions from coverage, is typically studied linguistically, not nonverbal communication, how something is said. More understanding is needed on how journalists maintain professional nonverbal neutrality norms during crises. Utilizing qualitative interviews with journalists analyzed through the lens of the needs of meaning framework, this study shows journalists are continually negotiating nonverbal neutrality boundaries. Results suggest journalists are not fully aware of nonverbal behaviors' impact on overall neutrality, trained in controlling nonverbal behaviors, nor receiving coping support. Suggestions for individual and organizational practices are provided.